Insights into reaction mechanisms of phosphenium cation and methyleneimine: a theoretical study. (14th October 2022) - Gu, Jinsong; Li, Yuan; Xu, Huilian; Liu, Shankui; Zhang, Xiujun; Tan, Xiaojun
Abstract: The mechanism of cycloaddition reaction between phosphenium cation and phosphindene with methyleneimine has been systematically investigated at the B3LYP/6-311++G(d, p) level of theory in order to better understand the reactivity for the valence isoelectronic of carbene. Phosphenium cation acts as an electrophilic reagent and accepts σ electrons of methyleneimine to form a complex in the first addition step. The greater the positive charge at phosphorus atom in phosphenium cation, the more stable the formed complex is. Introduction of substituents will decrease positive charge on phosphorus atom in phosphenium cation. The order of positive charge on phosphorus atom is HP + -F > HP + -OH > HP + -NH2, which is consistent with their Lewis acidities. The complex transforms to a three-membered ring product via a transition state in the second cyclization step. The product is less stable than the complex due to its tension of small ring. Graphical Abstract: UF0001